Legal regulation of usufruct in the legislation of European countries - Pankivskyi , Volodymyr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The institution of usufruct, developed by Roman jurists, has had a significant impact on the evolution of modern property law. For its proper implementation and development in Ukraine, a thorough analysis of the civil law systems of European countries that have adopted this institution and have long-standing experience in its effective application to the regulation of property relations is of crucial importance. Among such countries are, first and foremost, the Germany and the France, whose civil legislation provides for comprehensive and systematic regulation of the right of usufruct. The article outlines the main provisions of usufruct under the French Civil Code and the German Civil Code (Bürgerliches Gesetzbuch), including the concept of usufruct, the grounds for its creation and termination, as well as the rights and duties of the usufructuary and the owner. Emphasis is placed on the similarities and differences in their regulation. In addition, certain aspects of usufruct under the civil legislation of Italy and Poland are compared. The purpose of the study is to examine the peculiarities of the legal regulation of usufruct in the legislation of European countries. The research employs comparative-legal, formal-legal, and systemic-structural methods. It is concluded that, despite the differences characteristic of particular legal systems, there is, in general, a unified approach to the legal nature of usufruct. The general rule is confirmed that the right of usufruct is possible only in cases of using a thing while preserving its substance. During use, changes in the condition of the property are permissible as long as they do not affect the possibility of restoring it to its previous state after the termination of the usufruct. Attention is drawn to the fact that in French and German civil legislation, despite the broad scope of the usufructuary’s powers – including the right to use the property “as the owner himself” – the usufructuary does not become the owner of the property during the usufruct, but remains a user of another’s property. A similar approach can be observed in other European legal systems, particularly in the Italian Civil Code and the Polish Civil Code.